Long vowels and nasal-consonant sequences in Kisa - Ondondo, Emily A. (Academic publication, 2018)
Nasal Consonant (NC) sequences, in Bantu languages, and the long vowels preceding them remains a puzzle in Bantu literature and research. This paper provides a descriptively oriented analysis of the relationship between long vowels and nasal consonant sequences in Kisa, a dialect of Luhya, a Bantu language spoken in Khwisero Constituency Western Province, Kenya. The data used in this paper was generated by the author as a native speaker of Kisa. The central descriptive fact is that NC sequences in words consisting of native Kisa morphemes are usually, but not obligatorily, preceded by long vowels. As such, NC sequences usually appear as part of an overall VVNC sequence. This pattern is widely found in Bantu languages, and the modelling of this preference for VVNC sequences has been a significant topic in phonological research on Bantu languages. Kisa provides evidence against the predominant analysis of the VVNC preference in Bantu- compensatory lengthening. The paper shows that compensatory lengthening does not provide a well-motivated analysis of Kisa.
Keywords: Bantu; Kisa; Nasal Consonant Sequences; compensatory lengthening